Transformational government through eGov practice : socioeconomic, cultural, and technological issues - Shareef, Mahmud Akhter, 1966- (North American : Emerald, 2012)
The future of government as we know it is being shaped by the quickly-advancing progression of information and communication technology (ICT) eGovernment systems. eGov presents major challenges and advantages for policy makers and the public alike.